Transforming Government Decision-Making by Utilizing Artificial Intelligence (AI) in the Future - Oktaviani, Dewi (Indonesian Association for Public Administration (IAPA), 2024)
The development of AI utilization in the world is progressing very fast. Oxford Insight data in the Government AI Readiness Index 2023, globally Indonesia's index ranking is 42nd out of 193 countries in the world, with a total score of 61.03; and Indonesia is 8th out of 18 East Asian countries. The government (Indonesia) can use AI to transform decision-making into a policy. However, in utilizing AI, the government is still faced with the problem of the legal basis that still uses the Circular Letter of the Minister of Communication and Information Technology Number 9 of 2023 concerning Ethics of Artificial Intelligence, and the National Strategy document for Indonesian Intelligence 2020 - 2045 so that ethical issues need to be addressed. The government's challenge in transforming decision-making will indirectly impact the policy cycle that has been carried out so far. For this reason, a short-term strategy is needed, namely, the government needs to make a policy on the use of AI in the form of a Presidential Regulation. For the long term, the government can establish an Ethics Commission as an ad hoc supervisory institution, which can oversee the use of AI by ethics.